Dissecting maize diversity in lowland South America : genetic structure and geographic distribution models - Bracco, Mariana (2016)
Fil: Bracco, Mariana. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Ecología, Genética y Evolución. Buenos Aires, Argentina.